Analisis Putusan Hakim Tentang Perceraian Karena Tidak Mempunyai Anak Akibat Kista - Nurhidayah Matondang & Syapar Alim Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Law Number 1 of 1974 has explained the breakdown of marriage in article 38, one of which in letter (b) is divorce. Then, the reasons for divorce are clearly explained about the things that can be used as strong reasons for the parties to file a divorce to the Religious Court. As happened in case Number 203/Pdt.G/2020/PA.Pyb, the Petitioner (Ikhsan Ikhwandi Nasution/husband) submitted a request for divorce to the Panyabungan Religious Court on the pretext that the Respondent (Nurul Huda Hasibuan/wife) did not have children due to illness cyst he had. The type of research used is qualitative-descriptive research. The approach method used in this research is the juridical-empirical method, by analyzing the problem by combining legal materials (secondary) with primary data obtained from the field. The conclusion obtained in this study is that this decision is correct in terms of proof, seen from the fulfillment of the material and formal requirements. If viewed from the material requirements, the judge saw the correspondence between the petition and the witness testimony. The juridical review of the judge's decision was generally correct. Where the judge judge did not emphasize the cause of his divorce in terms of not having children due to his cyst disease, but rather on the side of husband and wife quarrels which in Arabic terms is called syiqoqwhich occurs continuously, because at the time of evidence at trial the Petitioner did not present authentic evidence in the form of a certificate from a doctor. Meanwhile, if viewed from the formal requirements, the judge decided the divorce case was more due to the fulfillment of the elements of article 19 letter (f) of Government Regulation Number 9 of 1975 concerning the implementation of the Marriage Law and Article 116 letter (f) of the Compilation of Islamic Law and 39 of law number 1 of 1974.